NUCLEAR WEAPONS, DETERRENCE AND THE ESCALATION OF ARMED CONFLICTS IN GLOBAL POLITICS: GATEWAY-TO-POWER SHIFT FROM THE WEST TO THE EAST AND THE THIRD WORLD WAR IN THE 21ST CENTURY - Ameh, Emmanuel Ugbedeojo (African Journal of Social and Behavioural Sciences, 2024)
The emergence of nuclear weapons has fundamentally reshaped global politics, influencing power dynamics, security paradigms, and conflict behaviours in the 21st century. This study explores the relationship of nuclear weapons, deterrence theory, and the escalation of armed conflicts within contemporary global politics. Drawing on theoretical frameworks including deterrence theory, balance of power theory, and conflict alleviation theory, the research investigates the mechanisms of nuclear deterrence, factors contributing to conflict escalation, and potential implications of a third-world war - being an eclectic approach that covers the major area. Case studies such as the Cuban Missile Crisis and various regional conflicts are analysed to underscore the challenges and risks posed by nuclear arsenals in international security. Utilising a qualitative approach with secondary data from existing literature and historical analyses, the study reveals that while nuclear deterrence can prevent direct military confrontations, the presence of nuclear weapons complicates global stability, necessitating robust crisis management and diplomatic interventions. The findings underscore the importance of effective arms control and disarmament efforts to mitigate nuclear risks. Accordingly, policymakers are urged to prioritise diplomatic initiatives, enhance crisis management strategies, renew commitments to arms control agreements, foster international cooperation, and address underlying socio-economic factors driving conflict dynamics.